The Role of Indonesia as a Presidency for ASEAN and Blue Economy’s driver: SDG’s Issues and Legal Perspective - Saraswati, Retno; Hananto, Pulung Widhi; Prananda, Rahandy Rizki; Mahramhafiz, Muhammad; Pennesi, Lorenzo (LAW REFORM, 2025)
The blue economy is an emerging concept that emphasizes the protection of marine life and ecosystems while promoting economic growth through the sustainable utilization of ocean resources. This principle is gaining increasing traction among ASEAN member states. Strategically positioned geographically, these nations possess significant potential to leverage their marine resources. However, disparities in technological capabilities and human resources continue to hinder the optimal utilization of these resources across the region.This paper identifies and analyzes the challenges and opportunities faced by ASEAN member states in implementing the blue economy within their respective territories and across the region. It also offers a new and in-depth perspective by examining Indonesia’s pivotal role during its ASEAN Chairmanship in advancing the blue economy agenda. Indonesia’s efforts go beyond merely emphasizing the importance of the blue economy; they also include strategic initiatives to promote cooperation, knowledge sharing, and the development of robust legal frameworks within ASEAN to foster sustainable marine governance and resource management.Indonesia’s leadership presents a unique opportunity to address critical issues and to catalyze the expansion of the blue economy in Southeast Asia, ensuring sustainable development and a balanced approach to the utilization of marine resources